The Execution of Saddam Hussein: An Appalling Milestone for Disturbing Developments. - Ioannis Mazis (Defensor Pacis, 2007)
Saddam Hussein’s execution on Saturday December 31, 2006 and its broadcast over the internet in the form of video footage “leaked” by one of the bystanders constitutes a milestone of important geostrategic developments in the Middle East, mainly as a multiplier of the Shia-Sunni tension, between the followers of Moktanta al Sadr and the Sunnis, between the Shiites of Tehran and the Lebanese Muslims (Shiites and Sunnis). The execution also triggered a chain reaction of the Kurdish ethnic pockets in the area, starting with Iraqi Kurdistan. This reaction engages Turkey in the issue of geostrategic reshuffling in the area and provides its military regime with the opportunity to use this threat to achieve EU tolerance as regards the country’s accession process without having to implement the necessary adjustments stipulated by the “acquis communautaire” and without trying to clear the “Cyprus hurdle” in the course of the entry talks. Greece and Cyprus must adopt a coordinated approach at all levels to deal with this situation, in which even “hot conflict provocations” by Turkey against Greece, but also an increase of pressure from across the Atlantic directed against Levkosia and Athens, cannot be ruled out.